Use of Interactive Learning Technology in Improving Literacy Skills in Elementary Students - Wiwik Tri Handayani (International Journal of Students Education, 2024)
This research aims to obtain information regarding the role of using technology-based learning media in developing digital literacy for students, especially in the teaching and learning process in elementary schools. The literature study approach is the method used in the research carried out. Where this research comes from several journals that are relevant to the topic discussed within the scope of the role of technology-based learning media in digital literacy learning in elementary schools. The research results obtained are that the use of technology as a learning medium in the literacy learning process in elementary school has an effect on the learning paradigm which is able to increase motivation, learning outcomes and digital literacy in students.